O trabalho cotidiano de profissionais de saúde em uma Unidade de Terapia Intensiva - Mayara Durães Bicalho Oliveira (2017)
This qualitative case study, which used notions of the comprehensive sociology and aimed to understand the daily work in the Intensive Care Unit from the perspective of health professionals. The study was conducted at an Adult Intensive Care Unit of a hospital reference in urgent / emergency care of the State of Minas Gerais.The participants were health professionals enrolled in the unit and were included in the inclusion criteria of the study, totaling twenty participants, two physiotherapists, five nurses, three doctors, one nutritionist, five nursing technicians, a social worker, two psychologists and a pharmacist. The data were collected through interviews with semistructured script, respecting the saturation criteria and submitted to the Bardins content analysis. The reflections of this analysis allowed the construction of three categories. They are: 1. feelings and Meanings that involve daily work; 2. relationships and teamwork in the ICU; 3. ICU: a half mystical place. The first category reveals the feelings, expectations and meanings that daily work has for health professionals. Satisfaction, motivation and professional recognition have emerged in the discourses, despite the constant challenges that daily work in the intensive care unit brings, be they: overcoming fears and yearnings, the search for integrality and humanization of care and confrontations of situations involving death, unpredictability and professional suffering. Situations related to exhaustion, professional burnout and work overload were described by the participants as experienced obstacles, capable of provoking professional ill-health. The daily work, besides providing a personal and professional learning, instigates a constant need to seek technical improvement. The second category considers the relational aspects experienced in intensive care. It was emphasized the importance of effective communication, as well as the need for the interaction of the participants and the effectiveness of collaborative and interdisciplinary practices for teamwork to take place. However, some obstacles hamper the implementation of this form of work. The third category deals with aspects related to the characterization of this service, such as the specificity of the hospital and the sector, which contributes to the reconfiguration and construction of daily work. In spite of the mystical imprint attributed to the institution / sector, it presents contradictions that awaken the reflection on such "mysticism". In general, this study allowed us to understand the daily work that health professionals construct in the intensive care unit and the influence of the particularities that involve the day to day. The work is complex and intense, however, singular and differentiated, involving a dichotomous relationship of pleasure and suffering. The daily doing is resignified at every moment. The reflection about the object made it possible to elucidate the characteristics, potentialities and challenges present in daily work, as well as its influence on the quality of care. It is hoped, with this research, to contribute to new reflections, questions and constructions about the work in the Units of Intensive Therapy.